Attempted DNA extraction from a Rancho La Brea Columbian mammoth (Mammuthus columbi): prospects for ancient DNA from asphalt deposits. Issue 4 (11th January 2014) - Gold, David A.; Robinson, Jacqueline; Farrell, Aisling B.; Harris, John M.; Thalmann, Olaf; Jacobs, David K.
Abstract Fossil‐bearing asphalt deposits are an understudied and potentially significant source of ancient DNA. Previous attempts to extract DNA from skeletons preserved at the Rancho La Brea tar pits in Los Angeles, California, have proven unsuccessful, but it is unclear whether this is due to a lack of endogenous DNA, or if the problem is caused by asphalt‐mediated inhibition. In an attempt to test these hypotheses, a recently recovered Columbian mammoth (Mammuthus columbi) skeleton with an unusual pattern of asphalt impregnation was studied. Ultimately, none of the bone samples tested successfully amplified M. columbi DNA. Our work suggests that reagents typically used to remove asphalt from ancient samples also inhibit DNA extraction. Ultimately, we conclude that the probability of recovering ancient DNA from fossils in asphalt deposits is strongly (perhaps fatally) hindered by the organic compounds that permeate the bones and that at the Rancho La Brea tar pits, environmental conditions might not have been ideal for the general preservation of genetic material.